2021
DOI: 10.30968/rbfhss.2021.122.0573
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant drug interactions involving antimicrobials in a general hospital: a cross-sectional study

Abstract: Objective: To assess the prevalence of pDDI involving antimicrobials and other standardized drugs in a large general hospital in the interior of São Paulo. Methods: quantitative study, with cross-sectional design and data collection by documentary analysis of hospital prescriptions from April to June 2017. Results: 66 clinically relevant pDDI were found, which corresponded to approximately 7.3% of antimicrobial prescriptions, being 93.9% (62) contraindicated / severe and 6.1% (4) moderate. There was no differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
1
0
2
Order By: Relevance
“…19,20,24 Furthermore, earlier studies by Baniasadi et al, and Pavanello et al, in critical care patients showed that the most common drug class involved in pDDIs was anti-infective for systemic use, accounting for 51.5% and 45.8%, respectively. 22,25 The difference in study settings, varying profiles of study populations, disagreement in treatment guidelines and prescribing practice, and the use of different clinical decision support tools to analyze drug interactions may help explain the difference in the class of drugs involved in the onset of pDDIs.…”
Section: Discussionmentioning
confidence: 99%
“…19,20,24 Furthermore, earlier studies by Baniasadi et al, and Pavanello et al, in critical care patients showed that the most common drug class involved in pDDIs was anti-infective for systemic use, accounting for 51.5% and 45.8%, respectively. 22,25 The difference in study settings, varying profiles of study populations, disagreement in treatment guidelines and prescribing practice, and the use of different clinical decision support tools to analyze drug interactions may help explain the difference in the class of drugs involved in the onset of pDDIs.…”
Section: Discussionmentioning
confidence: 99%
“…Como a maioria desses medicamentos possui eliminação renal e alguns são nefrotóxicos, os mesmos podem estar associados a RAMs graves nesses pacientes 12 . Um estudo que avaliou a prevalência de potenciais IMs envolvendo antimicrobianos e outros medicamentos padronizados em um hospital, identificou que 19,7% dos antimicrobianos da unidade estavam envolvidos em potenciais IMs clinicamente relevantes 13 .…”
Section: Rbfhssunclassified
“…13,2%) e penicilinas 23 (10,5%), e no sétimo dia carbapenêmicos 27 (17,3%) e lipopeptídeos 17(10,9%). Já as classes de antimicrobianos mais prevalentes nas IMs ao longo dos 7 dias foram: antifúngicos 162 (28,6%), seguido das fluoroquinolonas 97 (17,1%) e oxazolidinona 76 (13,4%) (tabela 4).…”
unclassified